The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1063/1.1834489
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio studies of a water layer at transition metal surfaces

Abstract: This paper presents a detailed study of a water adlayer adsorbed on Pt(111) and Rh(111) surfaces using periodic density functional theory methods. The interaction between the metal surface and the water molecules is assessed from molecular dynamics simulation data and single point electronic structure calculations of selected configurations. It is argued that the electron bands around the Fermi level of the metal substrate extend over the water adlayer. As a consequence in the presence of the water layer the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 64 publications
4
60
0
Order By: Relevance
“…58 This was attributed to the hydrogen-down configuration being energetically more stable than any other orientation of molecule. 59,60 Similarly, a relatively small positive peak follows a negative dip located near h = d (near the tip). This suggests that water molecules near the tip orient preferentially so that the hydrogen atoms are closer to the tip (here, the hydrogen up orientation is preferred).…”
Section: Resultsmentioning
confidence: 99%
“…58 This was attributed to the hydrogen-down configuration being energetically more stable than any other orientation of molecule. 59,60 Similarly, a relatively small positive peak follows a negative dip located near h = d (near the tip). This suggests that water molecules near the tip orient preferentially so that the hydrogen atoms are closer to the tip (here, the hydrogen up orientation is preferred).…”
Section: Resultsmentioning
confidence: 99%
“…42,43 The theoretical modelling of electrochemical reactions is equally complex, as it needs to account for the effect of the solvent on the adsorbed intermediates, the highly charged electric field in the double layer, the free energy of the electrons in the solid and the free energy of the solvated reactants as a function of potential. [44][45][46][47][48][49][50][51][52][53][54] However, it turns out that the overall trends can be 7 ‡ We note that a fuel cell would probably be operated at potentials lower than 0.9 V, to maximise the power output. However, catalysts are typically benchmarked at 0.9 V to minimise artefacts from the measurements.…”
Section: Theoretical Trends In Activity For Pt and Its Alloysmentioning
confidence: 99%
“…For water adsorbing on undeuterated Pt, STM studies have shown that on (100) step edges, water initially forms one-dimensional chains along the steps, whereas for (110) steps these are not clearly adsorbed [16]. On deuterium-covered Pt, the interaction of water with such surfaces will be driven by the (in)ability of water to form relatively stable two-dimensional hydrogen-bonded networks extending onto the terraces, versus the tendency of water to be structured into solvation shells of the adsorbed deuterium.…”
mentioning
confidence: 99%
“…On deuterium-covered Pt, the interaction of water with such surfaces will be driven by the (in)ability of water to form relatively stable two-dimensional hydrogen-bonded networks extending onto the terraces, versus the tendency of water to be structured into solvation shells of the adsorbed deuterium. We note that from density-functional theory (DFT) calculations, the interaction of water layers with Pt(111), i.e., the water-Pt bonding, is known to be very weak and its stability on such surfaces is mainly determined by the two-dimensional hydrogen bonding network [16]. Therefore, we expect that the fact that adsorbed deuterium inhibits the direct interaction of water with the platinum surface atoms, will have only a minor effect on its stability.…”
mentioning
confidence: 99%